EFFICACY OF AN AYURVEDIC INTERVENTION IN THE MANAGEMENT OF POLYCYSTIC OVARIAN SYNDROME (PCOS)- A CASE REPORT (International Journal of Ayurveda and Pharma Research, 2020)
In the present era, Polycystic ovarian syndrome (PCOS) is a documented as one of the most common hormonal endocrine disorders affecting 5-10 % of females due to life style and stress. It is characterized by hyper androgonism, polycystic ovaries, and chronic anovulation along with insulin resistance, abdominal obesity, hypertension, irregular menses, abnormal uterine bleeding and difficulty getting pregnancy. Most of the patients taking allopathic medicine but results are not so good. Laparoscopic ovarian drilling is the treatment of choice in case of PCOS in the conventional system. Noninvasive, safe and economically management is required. Ayurvedic approach to pathogenesis of PCOS can provide the solution to rising cases of this illness. Objective: to assess the clinical efficacy of Ayurvedic intervention in the management of Polycystic ovarian syndrome using with clinical symptoms and Ultrasonography (USG). Material and Method: it was a single case study. Kanchnara guggulu 750mg and Kanya lohadi vati 500mg along with Kanchnar kasaya 20 ml twice in a day with water for 90 days were used. Results: clinical symptoms were reduced and USG were significantly changed from baseline to end of the treatment.